2003
DOI: 10.1046/j.1439-0434.2003.00749.x
|View full text |Cite
|
Sign up to set email alerts
|

Vegetative Compatibility and Pathogenicity of Verticillium dahliae Kleb. Isolates from Olive in Israel

Abstract: Fifty‐two isolates of Verticillium dahliae from olive trees grown at different locations in Israel were assigned to vegetative compatibility groups (VCGs), using nitrate non‐utilizing (Nit) mutants. A higher frequency of nit1/nit3 mutants (95%) was obtained compared with NitM (5%), with 81% of the isolates being assigned to VCG4B and 19% to VCG2A. The pathogenicity of 14 randomly selected isolates (seven of each VCG) was tested on olive twigs (cv. Picual) and tomato. VCG4B and VCG2A isolates were similarly agg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 25 publications
0
7
1
Order By: Relevance
“…Currently, breeding programmes rely on natural infection of clones in trials to obtain information on disease susceptibility of future planting material. It has been shown that different VCGs can differ in their pathogenicity to hosts (Van Heerden and Wingfield 2001;Tsror Lahkim and Levin 2003;Elmer et al 1999). Although pathogenicity has not been linked to VCG types in this study, our results showed that a high diversity of VCGs exists outside South Africa.…”
Section: Discussioncontrasting
confidence: 50%
See 1 more Smart Citation
“…Currently, breeding programmes rely on natural infection of clones in trials to obtain information on disease susceptibility of future planting material. It has been shown that different VCGs can differ in their pathogenicity to hosts (Van Heerden and Wingfield 2001;Tsror Lahkim and Levin 2003;Elmer et al 1999). Although pathogenicity has not been linked to VCG types in this study, our results showed that a high diversity of VCGs exists outside South Africa.…”
Section: Discussioncontrasting
confidence: 50%
“…The high diversity observed in Mozambican and Namibian populations suggests that the centre of diversity of Chr. It has been shown that different VCGs can differ in their pathogenicity to hosts (Van Heerden and Wingfield 2001;Tsror Lahkim and Levin 2003;Elmer et al 1999). This is further supported by the high diversity for the Mozambique population from both native S. cordatum and non-native Eucalyptus species.…”
Section: Discussionmentioning
confidence: 78%
“…However, there is no evidence regarding the number of mutated loci that govern both phenotypes in C. coffeicola. Therefore, we followed the terminology proposed by Correll et al (9), and widely accepted in the research with nit mutants (6,19,33). Considering the types of mutants identified, the greatest success in complementation tests is in pairings between nit1 or nit3 with NitM mutants (6,9,33,34), so we searched for these mutants.…”
Section: Discussionmentioning
confidence: 99%
“…Verticillium dahliae isolate (no. 27, which was originally isolated from an infected olive tree, and assigned as VCG 2A) (Tsror (Lahkim) and Levin, 2003) was chosen due to its apparent aggressiveness in the field. It was cultured on potato dextrose agar (PDA) petri dishes for 4 days at 27°C.…”
Section: Methodsmentioning
confidence: 99%
“…The susceptibility of five olive cultivars (Barnea, Frantoio, Picual, Arbequina, and Manzanillo) to V. dahliae was tested under in vitro conditions, using stem cuttings. Senescence symptoms that are correlated to those obtained on trees in the orchard (Tsror (Lahkim) and Levin, 2003), were evaluated once a week on a scale of 0 to 4, where 0 = no symptoms, 1 = up 50% of the leaves roll in, 2 = more than 50% of the leaves roll in and some are desiccated, 3 = up 95% of the leaves desiccated, and 4 = completely dry leaves or defoliation. The data used for the statistical analysis, were recorded 3 weeks after the beginning of the experiment.…”
Section: Methodsmentioning
confidence: 99%